Dissemination and Comparison of Genetic Determinants of mcr-Mediated Colistin Resistance in Enterobacteriaceae via Retailed Raw Meat Products - Gelbíčová, Tereza; Baráková, Alžběta; Florianová, Martina; Jamborová, Ivana; Zelendová, Markéta; Pospíšilová, Lucie; Koláčková, Ivana; Karpíšková, Renáta (Frontiers in Microbiology, 2019)
The global food chain may significantly promote the dissemination of bacteria resistant to antibiotics around the world. This study was aimed at determining the prevalence and genetic characteristics of Enterobacteriaceae with mcr-mediated colistin (CT) resistance in retail meat of different origins. Bacteria of the Enterobacteriaceae family carrying the mcr-1 gene were detected in 21% (18/86) of the examined samples, especially in turkey meat and liver originating from EU and non-EU countries (19%) and in rabbit meat imported from China (2%). The examined samples of the meat and liver of chicken and other poultry and of pork and beef were negative for the presence of bacteria carrying the mcr-1 to mcr-5 genes. A huge number of isolates belonging to Escherchia coli (n = 54), Klebsiella pneumoniae (n = 6), and Citrobacter braakii (n = 1) carrying the mcr-1 gene were obtained. Despite the high heterogeneity of the tested isolates, the mcr-1 gene was localized on only three types of plasmids (IncX4, IncHI2, and IncI2). The most frequent type of plasmid was IncX4, which carried the mcr-1 gene in 77% of E. coli and K. pneumoniae isolates from turkey meat and liver samples from the Czechia, Germany, Poland, and Brazil. Our findings indicate highly probable interspecies transfer of IncX4 and IncI2 plasmids within one meat sample. The co-resistance of plasmid-mediated CT resistance encoded by the mcr-1 and ESBL genes was detected in 18% of the isolates. Another noteworthy finding was the fosA3 gene coding for fosfomycin resistance in a multidrug-resistant isolate of E. coli from rabbit meat imported from China. The observed high level of Enterobacteriaceae with plasmids carrying the mcr-1 gene in retail meat reflects the need for Europe-wide monitoring of mcr-mediated CT resistance throughout the whole food chain.